ANALISIS YURIDIS TERHADAP TINDAK PIDANA PENCABULAN ANAK DIBAWAH UMUR BERDASARKAN UNDANG-UNDANG NOMOR 35 TAHUN 2014 TENTANG PERLINDUNGAN ANAK (TINJAUAN KASUS : No : 2672/PID.B/2017/PN.MDN) - Trisha Dinda M; Pinsen Bintara Hindartono Zega; Sahat S M Siburian; Rahma yanti (LPPM Universitas Putera Batam, 2020)
Criminal offence is a part of crimes against morality, where the obscene action does not occur in adults but also happens to minors. Either directly or indirectly the children fall victim to the crime of fornication and experience various disorders against him both physically and non-physically. The objectives of this study are as follows: first, to know the criminal liability of the perpetrators of the minors; Both legal policies against criminal acts of child abuse of minors; The three fundamental judges in the punishment of the perpetrators of criminal acts of abuse under minors. The author uses normative juridical method of approach, to determine the application of the principles and norms contained in the legislation. The source of the legal material used consists of primary legal materials, secondary legal materials, and tertiary legal materials. The tools used in the research are the literature, books, documents and other Tertid sources, and the results of this research as a basis for solving the underlying problems in this research. Data analyzed in a quantatif will be presented in the form of a systematic description by explaining the relationship between different types of data, hereinafter all data selected and processed later in the analysis descriptively so that besides Describing and submitting answers to the problems expressed are expected to provide solutions to the problems in this research. In this study the author examines and analyzes the criminal offence of minors under the name of the convicted Amrin Samuran Pulungan at the Medan state court to punish perpetrators with imprisonment, fines and has been shown to be legitimate and Convince the guilty of committing a criminal offence based on the testimony, instruction and description of the defendant.